2002
DOI: 10.1016/s1096-7192(02)00127-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MGEA5 on 10q24.1–q24.3 encoding the β-O-linked N-acetylglucosaminidase as a candidate gene for type 2 diabetes mellitus in Pima Indians

Abstract: Several diseases including type 2 diabetes mellitus (T2DM) are associated with abnormal O-glycosylation of proteins. b-O-linked N-acetylglucosaminidase (O-GlcNAcase) encoded by MGEA5 on 10g24.1-q24.3 removes N-acetylglucosamine (O-GlcNAc), and we investigated this locus in Pima Indians who have the world's highest prevalence of T2DM. We detected two variants but there was no association with parameters of insulin resistance or diabetes in 1300 Pimas. We conclude that mutations in MGEA5 are unlikely to contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 25 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…Farook et al (43) previously examined the MGEA5 gene as a candidate gene in the Pima Indians and reported no evidence to support its involvement in susceptibility to diabetes or insulin resistance. Based on SNP discovery efforts conducted on 30 subjects, that study identified only two variants in the gene regions that were screened.…”
Section: Discussionmentioning
confidence: 99%
“…Farook et al (43) previously examined the MGEA5 gene as a candidate gene in the Pima Indians and reported no evidence to support its involvement in susceptibility to diabetes or insulin resistance. Based on SNP discovery efforts conducted on 30 subjects, that study identified only two variants in the gene regions that were screened.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting a role for O-GlcNAc in the development of type II diabetes, mutations and alternative splice variants of O-GlcNAcase are associated with the onset of type II diabetes (40,92). Goto-Kakizaki rats express a 90-kDa isoform, ⌬250 -345, of O-GlcNAcase that appears to lack O-GlcNAcase activity (37).…”
Section: O-glcnacase Catalyzes the Removal Of O-glcnac (Ec 32152 mentioning
confidence: 99%
“…Importantly, the genetic variation in the O-GlcNAase (Oga, also known as Mgea5) gene contributes to increased risk for type 2 diabetes [8]. However, in some populations, Oga is not significantly associated with type 2 diabetes [9].…”
Section: Introductionmentioning
confidence: 99%